Multi-kernel dictionary learning for classifying maize varieties - Zhu, Hua; Yue, Jun; Li, Zhenbo; Zhang, Zhiwang (International Journal of Agricultural and Biological Engineering, 2018)
The automatic classification and identification of maize varieties is one of the important research contents in agriculture. A multi-kernel maize varieties classification approach was proposed in this paper in order to improve the recognition rate of maize varieties. In this approach, four kinds of maize varieties were selected, in each variety 200 grains were selected randomly as the samples, and in each sample 160 grains were taken as the training samples randomly; the characteristics of maize grain were extracted as the typical characteristics to distinguish maize varieties, by which the dictionary required by K-SVD was constructed; for the test samples, the feature-matrixes were extracted by dimension reduction method which were mapped to the high-dimension space by muti-kernel function mapping. The high-dimension characteristic matrixes were trained by K-SVD method and the corresponding feature dictionary was obtained respectively. Finally, the test samples representing were trained and classified by l2,1 minimization sparse coefficient. The experiment results showed that recognition rate was improved obviously through this approach, and the poor-effect to maize variety identification from partial occlusion can be eliminated effectively. Keywords: multi-kernel, sparse representation, dictionary learning, maize classification DOI: 10.25165/j.ijabe.20181103.3091 Citation: Zhu H, Yue J, Li Z B, Zhang Z W. Multi-kernel dictionary learning for classifying maize varieties. Int J Agric & Biol Eng, 2018; 11(3): 183–189.